A new type of CGO solutions and its applications in corner scattering. (20th January 2022) - Xiao, Jingni
Abstract: We consider corner scattering for the operator ∇ ⋅ γ ( x )∇ + k 2 ρ ( x ) in R 2, with γ a positive definite symmetric matrix and ρ a positive scalar function. A corner is referred to one that is on the boundary of the (compact) support of γ ( x ) − I or ρ ( x ) − 1, where I stands for the identity matrix. We assume that γ is a scalar function in a small neighborhood of the corner. We show that any admissible incident field will be scattered by such corners, which are allowed to be concave. Moreover, we provide a brief discussion on the existence of non-scattering waves when γ − I has a jump across the corner. In order to prove the results, we construct a new type of complex geometric optics solutions.